A companion to medical anthropology - Singer, Merrill; Erickson, Pamela I. (Pamela Irene), 1951- (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2011)
"In a global environment of enormous health challenges, medical anthropologists offer important understandings of health systems and healing practices around the world. These leading international scholars assess our persisting problems of malnutrition, chronic and infectious diseases, and the influence of escalating levels of inequality, poverty, war, and genocide. A Companion to Medical Anthropology examines the key issues and controversies in medical anthropology today. Singer and Erickson present a thorough assessment of a specific area of medical anthropology, including expert overviews of major topics such as environmental health, global health, biotechnology, syndemics, nutrition, substance abuse, infectious disease, and sexuality and reproductive health. The authors also provide a guide to future trends and the emerging issues that will shape the future of medical anthropology and global health for years to come"--
18. Anthropology and the Study of Illicit Drug Use / J. Bryan Page -- pt. IV Healthwork: Care, Treatment, and Communication -- 19. Ethnomedicine / Marsha B. Quinlan -- 20. Medical Pluralism: An Evolving and Contested Concept in Medical Anthropology / Hans A. Baer -- 21. Biotechnologies of Care / Ruth Fitzgerald -- 22. Social Interaction and Technology: Cultural Competency and the Universality of Good Manners / Craig Palmer -- 23. Biocommunicability / Charles L. Briggs -- 24. Anthropology at the End of Life / Ron Barrett -- pt. V The Road Ahead -- 25. Operationalizing a Right to Health: Theorizing a National Health System as a "Commons" / Beverly Bell -- 26. As the Future Explodes into the Present: Emergent Issues and the Tomorrow of Medical Anthropology / Pamela I. Erickson.
Includes bibliographical references and index.
Print version record.
Keywords: Medical anthropology; Anthropology, Physical; Social Medicine; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Medical anthropology; Ethnomedizin; Electronic books